Biharmonic Maps and Laguerre Minimal Surfaces - Abu Muhanna, Yusuf; M. Ali, Rosihan (Hindawi Publishing Corporation, 2013)
A Laguerre surface is known to be minimal if and only if its corresponding isotropic map is biharmonic. For every Laguerre surface Φ is its associated surface Ψ = (1 + |